2006
DOI: 10.1016/j.clpt.2006.05.003
|View full text |Cite
|
Sign up to set email alerts
|

Association of enzyme and transporter genotypes with the pharmacokinetics of imatinib

Abstract: This study indicates that common genetic variants in the evaluated genes have only a limited impact on the pharmacokinetics of imatinib. Further investigation is required to quantitatively assess the clinical significance of homozygous variant ABCG2 and CYP2D6 genotypes in patients treated with imatinib.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
91
3

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 134 publications
(102 citation statements)
references
References 36 publications
7
91
3
Order By: Relevance
“…The reduced protein levels and altered ATPase activity of the BCRP C421A variant might affect the oral absorption and/or elimination pathways of gefitinib and thereby increase the steady-state gefitinib plasma concentrations leading to diarrhoea. In contrast, Gardner et al (2006) did not find significant differences in the pharmacokinetic parameters of imatinib in vivo between 16 patients heterozygous for the C421A SNP compared with 66 patients harbouring the wild-type sequence. This result was unexpected, since the authors showed that HEK293 cells transfected with wild-type BCRP accumulated significantly less imatinib than HEK293 cells transfected with the C421A BCRP variant, despite similar levels of protein expression.…”
Section: Bcrp Variantscontrasting
confidence: 59%
“…The reduced protein levels and altered ATPase activity of the BCRP C421A variant might affect the oral absorption and/or elimination pathways of gefitinib and thereby increase the steady-state gefitinib plasma concentrations leading to diarrhoea. In contrast, Gardner et al (2006) did not find significant differences in the pharmacokinetic parameters of imatinib in vivo between 16 patients heterozygous for the C421A SNP compared with 66 patients harbouring the wild-type sequence. This result was unexpected, since the authors showed that HEK293 cells transfected with wild-type BCRP accumulated significantly less imatinib than HEK293 cells transfected with the C421A BCRP variant, despite similar levels of protein expression.…”
Section: Bcrp Variantscontrasting
confidence: 59%
“…An initial study of 9 allelic variants in 82 patients found no correlation between polymorphisms in ABCB1, ABCG2, CYP2C9, CYP2C19 or CYP3A4 and imatinib clearance at steady-state. 20 However, a smaller subsequent study found a correlation between ABCB1 polymorphisms and steadystate clearance of imatinib. 21 In direct contradiction to the findings of Judson et al, in this study, an overall decrease in clearance was observed, from day 1 to steady-state.…”
Section: Discussionmentioning
confidence: 99%
“…16 Previous studies have investigated whether SNPs in ABCB1, including 1236T4C, 2677G4T/A and 3435T4C, affect IM pharmacokinetics; however, the role of ABCB1 genetic variation in IM trough concentration is still unclear. 17,18 OCT1, which is encoded by SLC22A1, is primarily expressed on hepatocytes, suggesting that it has a role in substrate uptake into the liver. [19][20][21] Although IM is a substrate of OCT1, 15,22,23 no association between IM and SLC22A1 286C4T or 1498G4A, variants not common in the Japanese population, was previously observed.…”
Section: Introductionmentioning
confidence: 99%